GENDER STEREOTYPES CHANGES OF MERIDA’S CHARACTER IN DISNEY MOVIE BRAVE - Winarsih, Tri; Sili, Surya; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This research is aimed to reveal of how Merida’s character deal with gender stereotypes, whether she fall within the stereotypes rule or not, the writer used the theory of Sex Role Inventory by Sandra L Bem to measure Merida’s masculine and feminine traits. Next purpose is to examine the process of Merida’s gender stereotypes changes by using the theory of Feminist Identity Development by Nancy E Downing and Kristin L. Roush. This research is categorized as a qualitative research and it applied the technique of coding in analyzing data. The result of this study found out that Merida’s character did not embrace the gender stereotypes due to her dominated masculine traits character rather than feminine as contradictory to gender stereotypes. Merida's character has ten masculine traits and three feminine traits. Furthermore, the process of Merida’s stereotype changes began from revelation stage and the climax is she survived to the stage of active commitment.